2014
DOI: 10.1152/ajplung.00290.2013
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and activity of secretory leukoprotease inhibitor (SLPI) is altered in smokers

Abstract: A hallmark of cigarette smoking is a shift in the protease/antiprotease balance, in favor of protease activity. However, it has recently been shown that smokers have increased expression of a key antiprotease, secretory leukoprotease inhibitor (SLPI), yet the mechanisms involved in SLPI transcriptional regulation and functional activity of SLPI remain unclear. We examined SLPI mRNA and protein secretion in differentiated nasal epithelial cells (NECs) and nasal lavage fluid (NLF) from nonsmokers and smokers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
(100 reference statements)
2
9
0
Order By: Relevance
“…Smoking is known to have direct effects on oral immune status (Lee et al , ). The higher salivary SLPI concentrations among current smokers observed in this study are consistent with findings from other studies that have reported increased SLPI secretions among smokers (Bouloukaki et al , ; Meyer et al , ). Smoking has been shown to enhance the expression of the signal transducer and activator of transcription (STAT1 protein), which, in turn, leads to increased SLPI expression (Meyer et al , ).…”
Section: Discussionsupporting
confidence: 93%
“…Smoking is known to have direct effects on oral immune status (Lee et al , ). The higher salivary SLPI concentrations among current smokers observed in this study are consistent with findings from other studies that have reported increased SLPI secretions among smokers (Bouloukaki et al , ; Meyer et al , ). Smoking has been shown to enhance the expression of the signal transducer and activator of transcription (STAT1 protein), which, in turn, leads to increased SLPI expression (Meyer et al , ).…”
Section: Discussionsupporting
confidence: 93%
“…During virus infection, we clearly demonstrate in a range of models that FP has a suppressive effect on airway SLPI production. Since STAT1 has previously been shown to regulate SLPI expression 52 , FP likely impairs SLPI production during RV infection by suppressing PRR-induced IFN production thereby reducing subsequent IFNAR-mediated STAT1 activation. This mechanism is supported by our finding that IFNAR1 −/− mice also had reduced RV induction of SLPI.…”
Section: Discussionmentioning
confidence: 99%
“…Sharma et al (109) found that CSE inhibits platelet-activating factor (PAF) acetylhydrolase activity, which enhances PAF production and PMN adherence. Similarly, Meyer et al (83) showed that the expression of secretory leukoprotease inhibitor (SLPI) is regulated by Stat1, and both are increased in nasal epithelial cells and BALF of smokers, indicating that altered SLPI regulation and activity induced by CS could play a role in the development of respiratory inflammation and infection.…”
Section: Key Studies and Recent Advances: A Literature Review From 20mentioning
confidence: 93%